(3efGbH GdGeGe GdTGaYis - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMehO cMjdi Hf HTjQ GdLjdi s)
(3ChdgG (B:s
(3GdMeO ddg dGNGdb ddCTjGA EdG gh s
(3BNQgG (B:s
(3hGYde Gf GdNhV ai Jbjjeg GdeSGFd hJYOjOgG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B506 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B294 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeY GdCMeOi HWfWG (B((3SjQ hJGQjN (B1) s
Keywords: (3GdJGQjNs